Irrigated Grain Sorghum Response to Long-Term Nitrogen and Phosphorus Fertilization - A. Schlegel; H. D. Bond (Kansas Agricultural Experiment Station Research Reports, 2017)
Long-term research shows that phosphorus (P) and nitrogen (N) fertilizer must be applied to optimize production of irrigated grain sorghum in western Kansas. In 2016, N applied alone increased yields 71 bu/a, whereas N and P applied together increased yields up to 93 bu/a. Averaged across the past 10 years, N and P fertilization increased sorghum yields up to 77 bu/a. Application of 80 lb/a N (with P) was sufficient to produce 89% of maximum yield in 2016, which is slightly less than the 10-yr average. Application of potassium (K) has had no effect on sorghum yield throughout the study period. Average grain N content reached a maximum of 0.7 lb/bu while grain P content reached a maximum of 0.15 lb/bu (0.34 lb P2O5/bu) and grain K content reached a maximum of 0.19 lb/bu (0.23 lb K2O/bu). At the highest N, P, and K rate, apparent fertilizer recovery in the grain was 33% for N, 69% for P, and 40% for K.
Keywords: nitrogen fertilization; phosphorus fertilization; irrigated grain sorghum; long term fertility; nutrient removal